Fabrication of Bi2Te3−xSex nanowires with tunable chemical compositions and enhanced thermoelectric properties. (18th January 2017) - Liu, Shuai; Peng, Nan; Zhou, Chongjian; Bai, Yu; Tang, Shuang; Ma, Dayan; Ma, Fei; Xu, Kewei
Abstract: Uniform Bi2 Te3− x Se x nanowires (NWs) with tunable components are synthesized by a modified solution method free of any template, and inter-diffusion mechanism is proposed for the growth and transformation of ternary nanowires. Spark plasma sintering is adopted to fabricate the pellets of Bi2 Te3− x Se x NWs and thermoelectric transport properties are measured. As compared to Bi2 Te3 pellets, Se doping results in lowered electrical conductivity because of the reduced carrier concentration, both the Seebeck coefficient and the power factor are enhanced substantially. The Bi2 Te2.7 Se0.3 pellet exhibits the highest power factor at room temperature as a result of optimized carrier concentration (4.37 × 10 19 cm −3 ) and mobility (60.22 cm 2 V −1 s −1 ). As compared to Bi2 Te3, the thermal conductivity of Bi2 Te3− x Se x is lowered owing to the enhanced phonon scattering by dopants and grain boundaries. As a result, the ZT value at 300 K is substantially improved from 0.045 of Bi2 Te3 to 0.42 of Bi2 Te2.7 Se0.3 . It is suggested that Se doping is an effective way to enhance the thermoelectric performance of Bi2 Te3 based materials.